R2R3 MYB transcription factors: key regulators of the flavonoid biosynthetic pathway in grapevine - Czemmel, Stefan; Heppel, Simon; Bogs, Jochen (Protoplasma, 2012)
Flavonoids compose one of the most abundant and important subgroups of secondary metabolites with more than 6,000 compounds detected so far in higher plants. They are found in various compositions and concentrations in nearly all plant tissues. Besides the attraction of pollinators and dispersers to fruits and flowers, flavonoids also protect against a plethora of stresses including pathogen attack, wounding and UV irradiation. Flavonoid content and composition of fruits such as grapes, bilberries, strawberries and apples as well as food extracts such as green tea, wine and chocolate have been associated with fruit quality including taste, colour and health-promoting effects. To unravel the beneficial potentials of flavonoids on fruit quality, research has been focused recently on the molecular basis of flavonoid biosynthesis and regulation in economically important fruit-producing plants such as grapevine (Vitis vinifera L.). Transcription factors and genes encoding biosynthetic enzymes have been characterized, studies that set a benchmark for future research on the regulatory networks controlling flavonoid biosynthesis and diversity. This review summarizes recent advances in the knowledge of regulatory cascades involved in flavonoid biosynthesis in grapevine. Transcriptional regulation of flavonoid biosynthesis during berry development is highlighted, with a particular focus on MYB transcription factors as molecular clocks, key regulators and powerful biotechnological tools to identify novel pathway enzymes to optimize flavonoid content and composition in grapes.